HLA-G 14 bp polymorphism: Implications and its associated risk to malaria severity among iron-fortified Ghanaian infants and young children - Adjoa Tetteh Danquah; David Courtin; Samuel Asamoah Sakyi; Gideon Kwesi Nakotey; Samuel Kofi Tchum; Nana Afriyie Duah; Alisé Lagrave; Christian Sewor; Benjamin Amoani (PLoS ONE, 2025)
Background of the study Malaria is a paramount health concern mostly among infants and young children. The World Health Organization recommends iron fortification for children with iron deficiency anaemia living in malaria-endemic regions like Ghana. However, the intricate interplay between genetic polymorphisms and nutritional interventions in malaria susceptibility and severity remains unclear. The Human Leukocyte Antigen-G (HLA-G) locus within the Major Histocompatibility Complex (MHC) genes has surfaced as a critical player in regulating immune responses and influencing disease outcomes. Therefore, we aimed to evaluate the effect of HLA-G 14 bp polymorphism and its associated risk of malaria severity among Ghanaian infants and young children on iron fortification. Methodology This secondary double-blinded cluster randomized controlled trial involved 432 archival samples from the Tain District and Wenchi Municipal in the Bono Region. Participants aged between 6 and 36 months and consuming semi-solid foods were recruited in the study while children with malaria infection or other known medical conditions were excluded. Capillary blood samples were taken for anaemia determination using a haematology autoanalyzer, malaria infection status, and parasitaemia were assessed via microscopy, and HLA-G 14 bp polymorphism using PCR. Hardy-Weinberg equilibrium and multivariate regression models were used to analyze the data obtained. Results The research findings indicate that among the iron-fortified children with HLA-G, 14 bp + /- and 14 bp-/- variants are likely to develop severe malaria. Also, the HLA-G 14 bp + /- variant was linked to a higher risk of anaemia development among participants who received iron supplements. Conclusion The study results indicated that iron-fortified individuals carrying the HLA-G 14 bp insertion/deletion polymorphism have an elevated risk of developing severe malaria, which in turn predisposes them to anaemia.